Political Strategy of Legislative Candidates Moch. Irfan in the 2019 Election from the National Democratic Party in Dapil II Tegal Regency - M. Zimamul Khaq (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
This research reveals Moch's political strategy. Irfan in the 2019 Election. First, he maximized his power by focusing his campaign team in his base village, running an economical campaign, engaging youth, getting support from religious leaders (NU) from the PKB/PPP Party, avoiding competition within the extended family, promoting the slogan "Restoration," and looking for potential legislative candidates. Second, he took advantage of opportunities such as social capital and a strong mass base, based on his experience as Village Head and incumbent DPRD candidate, as well as community support for candidates from their own village. Also, there are ten seats in electoral district II, participation in community activities, as well as support from the Jamiyyah Nahdlatul Ulama organization in the village of Couples and the badminton community based in his facilities. Third, efforts are made to minimize weaknesses and threats through community involvement through the campaign team and extended family. Fourth, the threat from the PKB and PPP parties, which are affiliated with Nahdliyin, is faced by motivating party members to compete with the Hanura Party, Democrat and PKS in fighting for the last seat in parliament. With this comprehensive strategy, Moch. Irfan succeeded in winning a legislative seat in the 2019 elections and involved many elements, from the campaign team to the extended family, to gain public support.